2006
DOI: 10.1111/j.1745-7254.2006.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog protein promotes bone marrow-derived endothelial progenitor cell proliferation, migration and VEGF production via PI 3-kinase/ Akt signaling pathways1

Abstract: Aim: To investigate the effects of Sonic hedgehog (shh) protein on bone marrow‐derived endothelial progenitor cells (BM‐EPC) proliferation, migration and vascular endothelial growth factor (VEGF) production, and the potential signaling pathways involved in these effects. Methods: Bone marrow‐derived Flk‐1+ cells were enriched using the MACS system from adult Kunming mice and then BM‐EPC was cultured in gelatin‐coated culture dishes. The effects of shh N‐terminal pep‐tide on BM‐EPC proliferation were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…21,23,[28][29][30] We demonstrated that recombinant Shh is capable of inducing a fast (15-minute) Akt phosphorylation in SMCs. We showed that Shhinduced Akt phosphorylation is entirely inhibited by the pan PI3K inhibitor Wortmannin, the PI3Kg selective inhibitor AS-252424 ( Figure 3A), and competition with the inactive mutant of PI3Kg 25 (supplemental Figure 7A), demonstrating that Shh-induced Akt phosphorylation is mediated via PI3Kg.…”
Section: Shh-dependent Activation Of Pi3kg and Erk1/2 Participates Inmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23,[28][29][30] We demonstrated that recombinant Shh is capable of inducing a fast (15-minute) Akt phosphorylation in SMCs. We showed that Shhinduced Akt phosphorylation is entirely inhibited by the pan PI3K inhibitor Wortmannin, the PI3Kg selective inhibitor AS-252424 ( Figure 3A), and competition with the inactive mutant of PI3Kg 25 (supplemental Figure 7A), demonstrating that Shh-induced Akt phosphorylation is mediated via PI3Kg.…”
Section: Shh-dependent Activation Of Pi3kg and Erk1/2 Participates Inmentioning
confidence: 99%
“…At the cellular level, recombinant Shh was shown to induce SMC and pericyte proliferation and survival [16][17][18][19] and to contribute to PDGF-BB-induced myofibroblast proliferation. 20 Even though Shh was shown to induce the migration of various cell types such as fibroblasts, 21 ECs, 22 endothelial progenitors, 23 and monocytes, 24 its role and mechanism in SMC migration in vitro and in MC recruitment in vivo have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the phosphatidylinositol-kinase/Akt signaling pathways are involved in such effects of sonic hedgehog. 45 Evidence on the involvement of CXCR4 and the ligand SDF-1 in the regulation of endothelial precursor migration also comes from investigations of CXCR4/SDF-1 signaling in EPCs. It has been shown that CXCR4 is expressed in EPCs and SDF-1 can induce increased migration of EPCs mediated by CXCR4.…”
Section: Ligand-receptor Interaction and Signaling Cascadesmentioning
confidence: 99%
“…Although it has been confirmed that the Hh pathway participates in cell migration and angiogenesis processes and is correlated with the severity of the associated tumor (27)(28)(29), additionally, disruption of Hh pathway has been shown to inhibit metastasis in pancreatic cancer and gastric cancer (29)(30)(31), the relationship between the Hh signaling pathway and aggressiveness of HCC cells remains unclear. It is necessary to investigate whether the signaling influences proliferative and invasive potential of HCC cells.…”
Section: Discussionmentioning
confidence: 99%